A religiosidade afro-brasileira na história do Rio Grande do Norte no início do século XXI: intolerância contínua versus resistência crescente - Oliveira Júnior, Geraldo Barboza de (Trabalhos de Antropologia e Etnologia, 2020)
This text aims to show the result of a personal research on Afro-Brazilian religiosity in the state of Rio Grande do Norte; but privileging a glance on the Candomblé that is installed and strengthened through communities of Terreiros that represent ethnic variations like Angola, Ketu, Nagô, Jeje and Omolocô. The constituent reality of the communities of terreiros shows a field with two disparate, complementary and constant situations: intolerance and resistance. With the greater visibility provided by social media this phenomenon is more exposed and presents data that demand the intervention of public policies and security for the afro-Brazilian religions. I can consider my research on Candomblé in two specific phases: initially curious/academic in the period from 1988 to 2001. And the second period from 2002 to the present, adding to the condition of researcher, militancy religious.